Effects of trampling on intertidal mussel beds: Importance of disturbance intensity - Mendez, María Martha (2018)
Trampling is one of the most frequent forms of human disturbance on rocky shores. This activity may directly reduce the abundance of dominant species, indirectly promote changes in the abundance of associated species and ultimately affect biological interactions. We assessed the effects of different intensities of human trampling on Brachidontes spp. mussel beds, a dominant feature on rocky intertidal flats of southwestern Atlantic coasts. We experimentally applied 6 levels of trampling intensity on a Patagonian rocky shore. Simulated trampling intensity ranged from 0 to 600 tramples per day, and plots were disturbed replicating local usage patterns (i.e. austral summer weekend recreation). By the end of the experiment, Brachidontes spp. coverage decreased as a result of increasing intensities of trampling and mostly replaced by bare rock. Even the lowest experimental intensity produced a loss of more than 40% of coverage. Changes in coverage were generally immediate and occurred after the first 2 trampling events, regardless of disturbance intensity. Our findings highlight that as few as 5 people walking on the mid-intertidal flat can produce a decline of the mussel bed cover in a specific area. Our findings also alert to the urgency of implementing effective management actions in this and other frequented areas dominated by similar habitat-forming species.